Azotobacter vinelandii ferredoxin I. Aspartate 15 facilitates proton transfer to the reduced [3Fe-4S] cluster. - Shen, B; Martin, L; Butt, J; Armstrong, F; Stout, C; Jensen, G; Stephens, P; La Mar, G; Gorst, C; Burgess, B (1993)
The [3Fe-4S]+/0 cluster of Azotobacter vinelandii ferredoxin I (AvFdI) has an unusually low and strongly pH-dependent reduction potential (E'0). The reduced cluster exists in two forms, depending upon pH, that exhibit substantially different magnetic circular dichroism (MCD) spectra. Recent studies have established that the MCD changes observed on decreasing the pH from 8.3 (alkaline form) to 6.0 (acid form) cannot be explained either by a change in spin state of the cluster (Stephens, P.J., Jensen, G.M., Devlin, F.J., Morgan, T.V., Stout, C. D., Martin, A.E., and Burgess, B.K. (1991) Biochemistry 30, 3200-3209) or by a major structural change (e.g. ligand exchange) (Stout, C.D. (1993) J. Biol. Chem. 268, 25920-25927). Here, we have examined the influence of aspartate 15 on the pH dependence of the spectroscopic and electrochemical properties of AvFdI by construction of a D15N mutant. Aspartate 15, which is salt-bridged to lysine 84 at the protein surface, is the closest ionizable residue to the [3Fe-4S] cluster. The results show that replacement of aspartate by asparagine results in an approximately 20-mV increase in E'0 for the [3Fe-4S]+/0 cluster at high pH concomitant with an approximately 0.8-pH unit decrease in the pK of the reduced form. The major pH dependence of E'0 is preserved as is the effect observed by MCD. These data eliminate the possibility that the MCD change is due to the presence of Asp-15 and support the conclusion that it originates in direct protonation of the [3Fe-4S]0 cluster, probably on a sulfide ion. Voltammetric studies show that interconversion between [3Fe-4S]+ and [3Fe-4S]0 at acidic pH involves rapid electron transfer followed by proton transfer (for reduction) and then proton transfer followed by electron transfer (for oxidation). Ionized aspartate 15 facilitates proton transfer. Thus, protonation and deprotonation are much slower for D15N relative to the native protein at pH > 5.5. Proton transfer reactions necessary for further reduction of the [3Fe-4S]0 cluster to the [3Fe-4S]- and [3Fe-4S]2- states are also retarded in D15N. The results suggest that the carboxylate-ammonium salt bridge afforded by Asp-15-Lys-84 conducts protons between the cluster and solvent H2O molecules. Overproduction of D15N FdI, but not native FdI, in A. vinelandii has a negative effect on the growth rate of the organism, suggesting that the rate of protonation or deprotonation of the [3Fe-4S]0 cluster may be important in vivo.